The Effect of High Temperature (HT) Freshwater Cooling Pump Pressure on Main Engine Jacket Water Temperature on The MT. Sunrise Warrior Ship - Ni Putu Nofita Yanti Dewi; Nasri; Sigit Purwanto; Antonius Edy Kristiyono; Novitasari Novitasari (International Journal of Science and Environment (IJSE), 2026)
This study analyzes the effect of high temperature (HT) freshwater cooling pump pressure on the main engine jacket water temperature on the MT. Sunrise Warrior tanker, addressing operational reliability issues due to a decrease in pressure from 2.5-3.5 bar to 1.8 bar which causes overheating above 85°C. Using a quantitative approach with simple linear regression on 30 purposive samples from the engine room logbook (July 2024-July 2025), instruments including pressure gauge (X: 2.1-3.3 bar) and temperature indicator (Y: 70-90°C), analyzed through SPSS with the classical assumption test, t-test, F-test, and R². The results show a strong negative correlation (R=0.996) with the equation Y=124.931-16.650X which explains 99.1% of the variation (R²=0.991), all tests are significant (t=-56.527, F=3195.333, p<0.001). Increasing pump pressure significantly reduces jacket water temperature, resulting in a validated prediction model different from previous qualitative studies, with implications for preventive maintenance in maritime engineering.